2010
DOI: 10.1111/j.1747-0285.2010.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyridines and Multidrug Resistance: Previous Attempts, Present State, and Future Trends

Abstract: Multidrug resistance is defined as the resistance of a tumor cell to the cytotoxic action of divergent drugs used in chemotherapy. Dihydropyridines are a class of calcium channel antagonists that were discovered to have a multidrug resistance reversing effect and prompted investigations resulting in the synthesis of hundreds of new derivatives. Most of the investigators tried to achieve two goals: a decrease in Ca 2+ channel-blocking activity and an increase in the multidrug resistance reversing effect. Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…DHPs have also shown a broad range of other pharmacological effects such as antioxidant, anticonvulsant, anti-inflammatory, antidiabetic and antitubercular properties Moghadam et al, 2006;Saini et al, 2008). MDR reversal has also been reported as one of the important pharmacological potentials of DHPs (Carosati et al, 2012;Zarrin et al, 2010). In 1980, Tsuruo et al (1983 reported for the first time that DHPs demonstrated MDR reversal effects on cancer cell lines.…”
Section: Introductionmentioning
confidence: 95%
“…DHPs have also shown a broad range of other pharmacological effects such as antioxidant, anticonvulsant, anti-inflammatory, antidiabetic and antitubercular properties Moghadam et al, 2006;Saini et al, 2008). MDR reversal has also been reported as one of the important pharmacological potentials of DHPs (Carosati et al, 2012;Zarrin et al, 2010). In 1980, Tsuruo et al (1983 reported for the first time that DHPs demonstrated MDR reversal effects on cancer cell lines.…”
Section: Introductionmentioning
confidence: 95%
“…The potential uses of the DHPs scaffolds in the chemotherapy are well-documented and stem from their suitability for reversing the drug resistance in the treatment of cancer. 14,15 Calcium channel blockers like verapamil 16 and nicardipine, 17 among others have been reported to successfully overcome drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It is quite interesting to note that the 1,4-dihydropyridine and hydrazine derivatives have gained prominence in the recent years for cancer chemotherapy (24)(25)(26)(27)(28)(29)(30). 1,4-Dihydropyridines have been proved to be a new class of multidrug resistance (MDR) reversals in cancer treatment (31).…”
Section: Introductionmentioning
confidence: 99%